Metal-halide perovskites under pressure: Effect of anisotropic deformation on optoelectronic properties - Siyu Zhang; Mengyu Liu; Jie Su; Zhenhua Lin; Haidong Yuan; Lixin Guo; Yue Hao; Jingjing Chang (APL Energy)
Significant differences from typical semiconductors are observed in organic lead halide perovskites, which arise from the hybrid nature and soft lattice that make them sensitive to external driving forces, such as temperature and pressure. Here, the study employs first-principles calculations to investigate the structural, electrical, optical, and mechanical properties of pressure-induced perovskite (FAPbI3). Cubic FAPbI3 (Pm3m) undergoes a series of phase transitions as pressure increases from 0 to 9 GPa: transitioning to a tetragonal phase at ∼2 GPa, an orthorhombic phase around 5 GPa, and eventually to a monoclinic phase near 8 GPa, accompanied by reductions in lattice constant, bond length, and octahedral angle. The anisotropic structural deformation adjusts the bandgap from 1.43 eV at 0 GPa to 1.10 eV at 5 GPa, resulting in a redshift, suggesting that photoelectric conversion efficiency could be enhanced under pressures less than 5 GPa. In addition, increased pressure enhances the ductility of FAPbI3, evident from the anisotropy ratio increasing from 1.2 at 0 GPa to 2.0 at 9 GPa. The significant tunability of FAPbI3 under modest pressure ranges, combined with its increased anisotropy and ductility, opens new paradigms for its optoelectronic applications in extreme environments.